Antibacterial activity of chitosan grafting nisin: Preparation and characterization - Zhu, X.; Wu, H.; Yang, J.; Tong, J.; Yi, J.; Hu, Z.; Fan, L.
Nisin grafted chitosan was prepared by using microbial transglutaminase as biocatalyst. The transglutaminase-catalyzed reaction displayed high efficiency, high selectivity, mild reaction condition and environmental friendliness. The results revealed that the degree of substitution (DS)of nisin-chitosan could be controlled by adjusting the reaction time, the reaction temperature and the molar ratio of nisin to chitosan. And nisin-chitosan in different pH showed excellent solubility. In addition, in vitro antibacterial activity assessment, nisin-chitosan with the concentration of 0.008 mg/mL showed pronounced inhibitory effect against Gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis)and Gram-negative bacteria (Escherichia coli). Furthermore, L929 mouse fibroblasts were cultured with nisin-chitosan, and the methylthiazol tetrazolium (MTT)assay showed that nisin-chitosan with the concentration from 0.005 to 0.01 mg/mL displayed low toxicity. The results may contribute to finding the application of nisin-chitosan in pharmaceutical and food industry fields..
Keywords: CHITOSAN; NISIN; MICROBIAL TRANSGLUTAMINASE; ANTIBACTERIAL ACTIVITY; LOW TOXICITY